Fair Value Measurement in Financial Reporting - Dana Dvořáková (European Financial and Accounting Journal, 2011)
Measurement in financial accounting has been the most discussed issue in recent decades. The last very important result of the convergence process between IFRS and U.S. GAAP was adopting IFRS 13 – Fair Value Measurement in May 2011. The objective of IFRS 13 is to unify the approaches to determining fair value under IFRSs. The aim of this paper is to offer a comprehensive evaluation of the pros and cons that this standard brings.
Keywords: M41; 650; Fair value; Historical cost; Accounting; Assets; Liabilities